2009
DOI: 10.1074/jbc.m109.019976
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Conformation Capture of All 13 Genomic Loci in the Transcriptional Regulation of the Multisubunit Bigenomic Cytochrome c Oxidase in Neurons

Abstract: Cytochrome c oxidase (COX) is the terminal enzyme of the electron transport chain composed of 13 subunits; three are mitochondria-encoded, and 10 are nucleus-inscribed on nine different chromosomes within the mammalian genome. The transcriptional regulation of such a multisubunit, multichromosomal, and bigenomic enzyme is mechanistically challenging. Transcription factories have been proposed as one mechanism by which genes from different genomic loci congregate to transcribe functionally related genes, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 42 publications
(41 reference statements)
1
37
0
Order By: Relevance
“…Despite of the growing realization of the importance of these and other higher order chromatin structures for transcriptional regulation, very little is known about their role in the nervous system. Until recently, there were only three studies in the literature that explored loop formations in brain tissue (Dhar et al, 2009;Horike et al, 2005;Jiang et al, 2010), with a few additional papers using the brain as negative control for their studies on the sensory epithelium of the nose (Lomvardas et al, 2006) or the hematopoetic system (Simonis et al, 2006). However, to date, nothing is known about chromatin loopings in human brain.…”
Section: Epigenome Organization and Higher Order Chromatin Structuresmentioning
confidence: 99%
“…Despite of the growing realization of the importance of these and other higher order chromatin structures for transcriptional regulation, very little is known about their role in the nervous system. Until recently, there were only three studies in the literature that explored loop formations in brain tissue (Dhar et al, 2009;Horike et al, 2005;Jiang et al, 2010), with a few additional papers using the brain as negative control for their studies on the sensory epithelium of the nose (Lomvardas et al, 2006) or the hematopoetic system (Simonis et al, 2006). However, to date, nothing is known about chromatin loopings in human brain.…”
Section: Epigenome Organization and Higher Order Chromatin Structuresmentioning
confidence: 99%
“…The 13 subunits are encoded by two genomes (three mitochondrial, 10 nuclear). The expression of the genes involves the coordination of expression of individual genes and genome-wide structural regulation (Dhar et al, 2009). Once subunits are translated and imported, they are assembled into a holoenzyme that includes haem units (a, a 3 ), and metals (Cu A , Cu B ).…”
Section: Potential Determinants Of Cox Synthesismentioning
confidence: 99%
“…However, the introduction of techniques like chromosome conformation capture (Dekker et al, 2002) and single-molecule RNA fluorescence in situ hybridization (FISH; Femino et al, 1998) now show that co-expressed genes are often found together in 3D nuclear space (e.g. Cai et al, 2006;Simonis et al, 2006;Dhar et al, 2009;Schoenfelder et al, 2010;Noordemeer et al, 2011;Li et al, 2012;Papantonis et al, 2012), closely associated with sub-nuclear structures known as 'transcription factories' (Cook, 2010;Edelman and Fraser, 2012). Such factories have been defined as sites where at least two different genes are transcribed at one time, and they contain many of the molecular components necessary for the production of the mature message (Cook, 2010;Melnik et al, 2011).…”
Section: Introductionmentioning
confidence: 99%